2020
DOI: 10.1136/bmjopen-2020-041714
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the concordance between individual-level and area-level measures of socio-economic deprivation in a cancer patient cohort in England and Wales

Abstract: ObjectivesMost research on health inequalities uses aggregated deprivation scores assigned to the small area where the patient lives; however, the concordance between aggregate area-level deprivation measures and personal deprivation experienced by individuals living in the area is poorly understood. Our objective was to examine the agreement between individual and ecological deprivation. We tested the concordance between metrics of income, occupation and education at individual and area levels, and assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…21 Furthermore, there is better concordance between area-level and individual-level measures of education when assessing patient health outcomes. 46 The observed deprivation level of a patient in our study is likely to be consistent had they been diagnosed at a different time; this is because deprivation scores have a high concordance between updates (ie, IMD of 2007, 2010 and 2015). 21 Our results are comparable to studies using this area-level measure of deprivation.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…21 Furthermore, there is better concordance between area-level and individual-level measures of education when assessing patient health outcomes. 46 The observed deprivation level of a patient in our study is likely to be consistent had they been diagnosed at a different time; this is because deprivation scores have a high concordance between updates (ie, IMD of 2007, 2010 and 2015). 21 Our results are comparable to studies using this area-level measure of deprivation.…”
Section: Discussionsupporting
confidence: 52%
“…Second, recent research highlights the interest in using individual-level socioeconomic measures for assessing patient health outcomes in addition to arealevel measures of deprivation. 46 However, information on individual-level socioeconomic measures was unavailable, so we used only an area-level measure of socioeconomic status, which encapsulates the multidimensional composition of a patient's deprivation level in addition to the contextual level. 21 Furthermore, there is better concordance between area-level and individual-level measures of education when assessing patient health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The Indices of Multiple Deprivation is an area-based measure derived from the postcode of the patient's general practice, which may not accurately reflect the circumstances of the individual patients included in our analysis. 54,55 However, this potential misallocation should manifest in an underestimate of SES disparities due to regression dilution bias, meaning our main conclusions are not affected. Finally, there were a relatively low number of patients from EMGs, which did not facilitate a comparison of whether SES disparities differed by specific ethnicity (eg, Asian, Black).…”
Section: Dovepressmentioning
confidence: 81%
“…We highlight the importance of interpreting findings at the population level to minimize ecological fallacy risk. It has recently been shown that, in England and Wales, the average socioeconomic status at the area level correlates poorly with the individual SES in higher heterogeneity areas (i.e., ecological fallacy) [ 37 ]. Moreover, in our study, the SDI was derived for 2011, while cancer incidence is measured for the period 2010–2013.…”
Section: Discussionmentioning
confidence: 99%